Penerapan Aplikasi Smart Dan Mal Pelayanan Publik: Inovasi Kebijakan Berbasis Bukti Di Pemerintah Kota Bogor - Samsudin, Samsudin; Jumino, Tri Kisowo Kusuwo; Utami, Yuanita; Nurdin, Ismail (Pascasarjana STIE Amkop Makassar, 2024)
This research aims to evaluate the implementation of the SMART application and the Public Service Mall as evidence-based policy innovations in Bogor City. The method used is descriptive qualitative with data collection techniques in the form of interviews, observation, and documentation. The results show that the SMART application simplifies the licensing process through transparency and accountability, while the Public Service Mall improves the efficiency of public services by integrating various services in one location. The discussion highlights the importance of public digital literacy and government support to maximize these services. The study concludes that evidence-based innovation has improved the quality of public services, but challenges such as technology adaptation still need to be addressed.